MACROZOOBENTHOS ASSOCIATED WITH MANGROVE ECOSYSTEMS IN DUMAI WATERS - Sari, Dwi Julita; Zulkifli, Zulkifli; Efriyeldi, Efriyeldi (Asian Journal of Aquatic Sciences, 2022)
Mangrove ecosystems are unique ecosystems found along the coast or river mouths that are still influenced by tides. Association is a process of interaction between organisms and their environment which is not simple but a complex process. One of the biota associated with mangroves is macrozoobenthos. This research was conducted in August 2021. The purpose of the study was to determine environmental conditions, mangrove species and density, macrozoobenthic species and density, and the relationship between macrozoobenthic density and mangrove forest density in Dumai waters. Based on the results of the study, the types of macrozoobenthos were found from the gastropod and bivalves classes. The type that is found in all stations is Nerita lineata. The highest density is at station III, which is 19.11 ind/m2. Mangroves in Dumai waters are classified as dense with the dominant species being Rhizophora apiculata and Xylocarpus granatum. The relationship between the density of macrozoobenthos and the density of mangroves belongs to the medium category.